The Correlational Study Between EFL Students’ Metacognitive Awareness and Argumentative Writing Performance - Arrosyidah, Himma Jihadiah; Munir, Ahmad; Mustofa, Ali (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Metacognitive awareness has been recognized as a predictor of learning outcome, especially in tertiary level of education, and particularly in second and foreign language teaching and learning of writing. This component is crucial for EFL students whose first language is not English. In order to fulfill the demands of their own academic careers and future studies, there is a rising requirement for students to acquire more in-depth topic knowledge and to improve their text-analysis, planning, monitoring and evaluation skills. However, few studies have been conducted to examine metacognitive awareness in relation to argumentative writing. This study reports a quantitative study that investigates the correlation between EFL students’ metacognitive awareness and argumentative writing performance. Data collected in this study include a questionnaire and argumentative writing scores. Participants were 30 EFL students at one of the universities in Indonesia. The findings reveal that students’ metacognitive awareness is at an intermediate level while it was statistically insignificant that a relationship between their metacognitive awareness and their argumentative writing performance. The results suggest urgent action from EFL teachers and stake-holders to seek a feasible solution to foster students’ implementation of their metacognitive awareness into their writing and other language skills.Keywords: Argumentative writing, correlational study, EFL students, metacognitive awareness.